Diurnal variations in canine hematological parameters after commercial feed feeding - Costa, Letícia Ramos; da Silva, Nathalia Lopes Tavares [UNESP]; de Oliveira, Paula Lima; Minucci Bonatto, Natália Camila; Vieira, Guilherme Coutinho; Floriano, Beatriz Perez; de Barros, Luiz Daniel; Melo Bosculo, Maria Rachel; de Almeida, Breno Fernando Martins (Universidade Estadual de Londrina, 2020)
Complete blood count (CBC) is the evaluation of blood cells, which provides resourceful information. Considering that inadequate fasting time is the most common pre-analytical error in laboratory diagnosis and is associated with lipemia in blood samples, which has not yet been adequately investigated in dogs, this study aimed to assess diurnal postprandial changes in the CBC of healthy dogs fed with industrialized feed. Eighteen clinically healthy dogs aged 2-6 years and weighing over 6 kg were enrolled in the study. All dogs received “Premium” industrialized feed every 12 hours. Blood was collected after a 12-hour fasting period at 6:00 am (baseline), followed by feeding and new blood samples collected hourly for the next 11 consecutive hours. Red blood cell (RBC) counts, red cell distribution width (RDW), white blood cell (WBC) counts, platelets, mean platelet volume (MPV) and hemoglobin were obtained using an automated veterinary cell counter. Hematocrit (HTC) was determined by Strumia’s microcapillary method, differential leukocyte count was performed on hematological dye-stained blood smears and total plasma protein (TPP) was determined using refractometry. Variables were tested for normality and differences were considered significant when p < 0.05. A statistically significant decrease was observed in the erythrogram from 2 h for RBC and hemoglobin, from 3 h for HTC and from 4 h for MCV, persisting until the end of 11 hours. There was no change in MCHC and RDW. Regarding the leukogram, a significant increase in WBC was observed from 2 to 7 h, due to the increase in segmented neutrophils 2 to 8 h following feeding. Lymphocyte counts decreased significantly at 2 and 6 h following feeding. No alteration was observed in eosinophil, basophil, monocyte and platelet counts, as well as in MPV. From 5 h to 11 h after feeding, a significant decrease was seen on TPP. However, changes in hematological parameters did not exceed reference ranges for the canine species. Feeding dogs with industrialized feed caused statistically significant changes in erythrogram, leukogram and plasma protein content. While these changes do not seem to exceed reference values for the species in healthy animals, caution is warranted for sick animals with borderline values, in which these changes might be clinically important depending on the pathologic process.
Variações diurnas nos parâmetros hematológicos caninos após alimentação com ração comercial
Keywords: Complete blood count; Dog; Food